Machining contact and non-contact inspection technologies in industrial application - Terzić, Slavica; Dedić, Jasmina; Lazarević, Dragan; Šarkoćević, Živče; Nedic, Bogdan (Journal of Production Engineering, 2023)
Even though coordinate measuring machines (CMM) still achieve the most accurate measurement results, non-contact (optical) measuring systems are applied more and more in industry. The reasons of using optical scanners are in the higher speed of acquisition, higher density of data-points and better surface description, the ability to scan complex and non-rigid surfaces etc in comparison to contcact devices. This paper gives a review of state-of-the-art measuring contact and non-contact inspection technologies in industrial applications. Listed are the devices, principles and systems that are used at the data-acquisition (triangulation, time-of-flight and interferometry). The description of contact measuring machines (portable CMM and stationary CMM) and devices for non-contact scanning (laser scanner, structured light scanner and CT scanner) is given, and their advatages and disadvantages are mentioned with corresponding literature review.